Electrochemical Determination of Ranitidine Hydrochloride in Pharmaceutical Formulations and Biological Fluids at Graphene Modified Electrode - Xi, Xia; Ming, Liang (Asian Journal of Chemistry, 2013)
A simple and sensitive method is described for electrochemical determination of ranitidine hydrochloride, a widely used histamine H2-receptor antagonist, based on its electrochemical oxidation at a graphene modified glassy carbon electrode (GCE). Under optimized conditions, the anodic peak current was linear to the concentration of ranitidine hydrochloride in the range from 3.0 × 10-7-1.0 × 10-4 mol/L with the detection limit of 1.0 × 10-7 mol/L. The relative standard deviation (RSD) was 2.6 % for 2.0 × 10-5 mol/L ranitidine hydrochloride (n = 10). To further validate its possible application, the proposed method was successfully used for the determination of ranitidine hydrochloride in pharmaceutical formulations and biological fluids with satisfactory results.